Sistem Informasi Website Sekolah SD Inpres Homba Tana Menggunakan Framework CodeIgniter - Jefri Mone; Cecilia Dai Payon Binti Gabriel; Emirensiana Dapa Ege (Jurnal Sistem Informasi dan Ilmu Komputer, 2025)
Websites are critical in providing information to many people through the internet media. Internet. Where, the internet is one of the global computer network media that connects millions of devices around the world, thus enabling the exchange of information quickly and easily. Researchers created a website-based information system at Inpres Homba Tana Elementary School using the CodeIgniter Framework. The results of this study show that the school website can be used well because the results provide information that is easy to reach and more accurate.